Round-robin-differential-phase-shift quantum key distribution based on wavelength division multiplexing. (4th September 2018) - Lai, Hong; Luo, MingXing; Xu, Yongjian; Pieprzyk, Josef; Zhang, Jun; Pan, Lei; Orgun, Mehmet A
Abstract: Most quantum communications are resilient against eavesdropping attacks. But most protocols fail to address the problems of the poor rates of data transmission and key generation with the constraints of transmission distance and misattribution errors. To address these issues, we propose a new round-robin-differential-phase-shift (RRDPS) quantum key distribution (QKD) protocol to improve the transmission and key generation rates, secure transmission distance and misattribution errors. The new protocol named WDM-OAM-MDI-RRDPS QKD protocol is based on a combination of the wavelength division multiplexing (WDM) technique, Fibonacci-valued orbital angular momentum (OAM) theory, decoy state and measurement-device independent (MDI) method. It utilizes a series of coherent weak sources simultaneously and high-capacity Fibonacci-valued encoding technology. In our protocol, WDM technology can greatly increase the amount of information transmitted in optical fiber communication, and improve the transmission efficiency, the total secure bit rate and the key generation rate of QKD. The OAM theory can achieve basis independence and increase the information capacity per photon from one to five. Fibonacci-valued OAM states can be used to reduce misattribution errors. The decoy state and MDI method can be used to increase the transmission distance resilient to the Photon-number-splitting and detector blinding attacks.